(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
In the article entitled "Three keys and one lock features of the application of the modern teaching method", we tried to show different approaches to the application of the method related to the nature of the material being taught and the age group of students. The peculiar features of the application of the method were made visible on the basis of the analysis of literary works included in the school curriculum of Armenian literature.